Acetylation of the influenza A virus polymerase subunit PA in the N‐terminal domain positively regulates its endonuclease activity. (27th July 2021) - Hatakeyama, Dai; Shoji, Masaki; Ogata, Seiryo; Masuda, Takeshi; Nakano, Masahiro; Komatsu, Tsugunori; Saitoh, Ayaka; Makiyama, Kyoko; Tsuneishi, Hazuki; Miyatake, Asuka; Takahira, Mizuki; Nishikawa, Erina; et al.
Abstract : The post‐translational acetylation of lysine residues is found in many nonhistone proteins and is involved in a wide range of biological processes. Recently, we showed that the nucleoprotein of the influenza A virus is acetylated by histone acetyltransferases (HATs), a phenomenon that affects viral transcription. Here, we report that the PA subunit of influenza A virus RNA‐dependent RNA polymerase is acetylated by the HATs, P300/CREB‐binding protein‐associated factor (PCAF), and general control nonderepressible 5 (GCN5), resulting in accelerated endonuclease activity. Specifically, the full‐length PA subunit expressed in cultured 293T cells was found to be strongly acetylated. Moreover, the partial recombinant protein of the PA N‐terminal region containing the endonuclease domain was also acetylated by PCAF and GCN5 in vitro, which facilitated its endonuclease activity. Mass spectrometry analyses identified K19 as a candidate acetylation target in the PA N‐terminal region. Notably, the substitution of the lysine residue at position 19 with glutamine, a mimic of the acetyl‐lysine residue, enhanced its endonuclease activity in vitro ; this point mutation also accelerated influenza A virus RNA‐dependent RNA polymerase activity in the cell. Our findings suggest that PA acetylation is important for the regulation of the endonuclease and RNA polymerase activities of the influenza A virus. Abstract : The PA subunit of influenza A virus possesses an endonuclease activity, which plays an important role for 'cap snatching'. In this report, we discovered that PA endonuclease domain is acetylated by the host acetyltransferases P300/CREB‐binding protein‐associated factor and general control nonderepressible 5, which facilitate PA endonuclease activity. This modification is suggested to accelerate viral RNA polymerase activity in the cell. Our findings might provide new insights to understand regulation of viral transcription and replication.